Characteristics of heart rate response in elite Japanese Paralympic athletes with and without spinal cord injury during arm crank ergometer test - Kameda, M.; Iizuka, S.; Matsubayashi, T.; Hakamada, N. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: It is well documented that heart rate (HR) is a useful tool for determining training prescription in able-bodied participants. However, limited HR-based training prescription or assessment is available for Paralympic sitting sports athletes who depend mainly on upper body work. In addition, their HR response could be different for their disabilities, e.g., with/without spinal cord injury. Previous research indicates that a slightly lower HR max is generally obtained during arm than during leg exercise testing [1]. Thus, this study aimed to compare the HR response of elite Japanese Paralympic athletes with spinal cord injuries to those without them during an arm crank ergometer incremental test.